Green transformational leadership influences green work engagement and green creativity to drive environmental sustainability - M, Ramya; Prabu, G (International Journal of Management and Sustainability, 2025)
The purpose of the study is to address an unexplored aspect of environmental sustainability as the concerns towards the environment is burgeoning to conserve and protect the environment to have an ecological balance with the environment. The study identifies the relationship between GTL, green creativity, GWE and environmental sustainability. The study was carried out with the IT sector across Chennai and Bengaluru with a purposive sampling technique holds a respondent of 324 samples. The study confirms the role of GTL further enhances the increased motivation among employees and in turn employees are more likely to exhibit responsible behavior and also help in achieving environmental sustainability in the organisation. The study exhibits a positive relationship between GWE and ES bringing additional evidence that ought to measure successfully on the business’s environmental performance. The study’s findings conclude that the GWE and green creativity combinedly boosts the environmental sustainability in line with the role of green transformational leadership as it stands as a motivating factor for the employees and encourage them to achieve environmental sustainability. GTL’s distinctive impacts the employees to go beyond their interest and generate out-of-the-box solutions and improve environmental well-being.